Evidence for singular-phonon-induced nematic superconductivity in a topological superconductor candidate Sr0.1Bi2Se3 - Jinghui Wang (Nature Portfolio, 2019)
Superconductivity mediated by phonons is usually conventional due to isotropic electron-phonon coupling. Here, Wang et al. report highly anisotropic phonons only along [001] direction in Sr0.1Bi2Se3, indicating a singular electron-phonon coupling which favors a p-wave nematic superconductivity scenario.